Clinicopathological significance of the overexpression of MUC1 in upper tract urothelial carcinoma and possible application as a diagnostic marker. Issue 12 (28th September 2022) - Kobayashi, Go; Hayashi, Tetsutaro; Sentani, Kazuhiro; Takemoto, Kenshiro; Sekino, Yohei; Uraoka, Naohiro; Hanamoto, Masanori; Nose, Hiroyuki; Teishima, Jun; Arihiro, Koji; Hinata, Nobuyuki; Oue, Naohide
Abstract: Mucin 1 (MUC1) overexpression has been reported in many malignancies and is associated with a poor prognosis. However, the clinicopathological significance of MUC1 in upper tract urothelial carcinoma (UTUC) has not been investigated. We analyzed the expression and distribution of MUC1 in UTUC by immunohistochemistry. In normal urothelium, MUC1 expression was observed on the surface of umbrella cells. Meanwhile, the strong expression of MUC1 was observed in cell membranes and cytoplasm in UTUC tissues, and it was detected in 64 (58%) of a total of 110 UTUC cases. MUC1‐positive UTUC cases were associated with nodular/flat morphology, high grade, high T stage, and lymphatic and venous invasion and poor prognosis. Additionally, MUC1 expression was associated with high expression of Ki‐67, programmed death‐ligand 1 (PD‐L1), CD44 variant 9 (CD44v9), human epidermal growth factor receptor 2 (HER2), epidermal growth factor receptor (EGFR), and p53 in UTUC. Furthermore, immunocytochemistry for MUC1 on urine cytology slides demonstrated that the strong staining of MUC1 was more frequently found in tumor cells than in nonneoplastic cells. The diagnostic accuracy of urine cytology was improved by combining MUC1 immunostaining with cytology. These results suggest that MUC1 may be a prognostic biomarker in UTUC, and MUC1 exression has a potential application as a diagnostic immunomarker for urine cytology.